Tuning the Crystal Structure of A2CoPO4F (A = Li, Na) Fluoride‐Phosphates: A New Layered Polymorph of LiNaCoPO4F. Issue 39 (30th August 2019) - Fedotov, Stanislav S.; Aksyonov, Dmitry A.; Samarin, Aleksandr Sh.; Karakulina, Olesia M.; Hadermann, Joke; Stevenson, Keith J.; Khasanova, Nellie R.; Abakumov, Artem M.; Antipov, Evgeny V.
Abstract : Co‐containing fluoride‐phosphates are of interest in sense of delivering high electrode potentials and attractive specific energy values as positive electrode materials for rechargeable batteries. In this paper we report on a new Co‐based fluoride‐phosphate, LiNaCoPO4 F, with a layered structure (2D), which was Rietveld‐refined based on X‐ray powder diffraction data [ P 21 / c, a = 6.83881(4) Å, b = 11.23323(5) Å, c = 5.07654(2) Å, β = 90.3517(5) °, V = 389.982(3) Å 3 ] and validated by electron diffraction and high‐resolution scanning transmission electron microscopy. The differential scanning calorimetry measurements revealed that 2D‐LiNaCoPO4 F forms in a narrow temperature range of 520–530 °C and irreversibly converts to the known 3D‐LiNaCoPO4 F modification ( Pnma ) above 530 °C. The non‐carbon‐coated 2D‐LiNaCoPO4 F shows reversible electrochemical activity in Li‐ion cell in the potential range of 3.0–4.9 V vs. Li/Li + with an average potential of ≈ 4.5 V and in Na‐ion cell in the range of 3.0–4.5 V vs. Na/Na + exhibiting a plateau profile centered around 4.2 V, in agreement with the calculated potentials by density functional theory. The energy barriers for both Li + and Na + migration in 2D‐LiNaCoPO4 F amount to 0.15 eV along the [001] direction rendering 2D‐LiNaCoPO4 F as a viable electrode material for high‐power Li‐ and Na‐ion rechargeable batteries. The discovery and stabilization of the 2D‐LiNaCoPO4 F polymorph indicates that temperature influence on the synthesis of A2 MPO4 F fluoride‐phosphates needs more careful examination with perspective to unveil new structures. Abstract : A novel layered polymorph of LiNaCoPO4 F was stabilized by adjusting the synthesis temperature conditions. It gives promise for designing new positive electrode materials with fast ion transport and low volume variation for both Li‐ and Na‐ion batteries. Synthesis temperature remains an "unexplored dimension" for the A2 MPO4 F fluoride‐phosphates.